The impact of energy efficiency and renewable energy on GDP growth: new evidence from RALS-EG cointegration test and QARDL technique - Kadir, Musbau Omotola; Deka, Abraham; Ozdeser, Huseyin; Seraj, Mehdi; Turuc, Fatma (Springer, 2023)
In recent years, energy has been observed as a major driver of promoting economic growth. While energy is significant in enhancing economic growth, non-renewable energy has been blamed for its devastating effects on the environment, since it emits carbon dioxide. Thus, recent studies have encouraged the use of renewable energy, as an alternative source of energy, which is environmentally friendly. Energy efficiency, the wise utilization of energy without wasting it and producing the maximum possible output per each unit employed, is vital for economic growth. However, there is still a dearth in the literature, on how energy efficiency impacts economic growth, hence the present research's originality. The current research employs panel data of the emergency seven economies from 1990 to 2019, to investigate the effect of energy efficiency on economic growth. The emerging economies have in recent years emerged from being developing countries to becoming emerging economies through the vast use of energy in enhancing economic growth of their nations, a good example is China. Secondly, the research uses Residual Augmented Least Square-Engle and Granger to test cointegration, and Quantile Autoregressive Distributive Lag technique to ascertain the association among the series, which are the most contemporary models of data analysis and gives more robust findings. The research outcomes allude that labor, capital, non-renewable energy, carbon emissions, energy use, renewable energy, and energy efficiency gives significant positive effect on gross domestic product. We recommend the use of renewable energy which promotes economic growth and reduces the emissions of carbon-dioxide.
Keywords: GDP; Energy efficiency; Renewable energy; RALS; QARDL